Redescription of Tachardiella ourinhensis Hempel, 1937 (Hemiptera: Kerriidae) and its transfer to Neotachardiella gen. nov., with descriptions of two new species of Neotachardiella on Myrtaceae from Brazil and Uruguay - Kondo, Takumasa; da Silva, Vitor Cezar Pacheco; Júnior, Alberto Luiz Marsaro; Takahashi, Satomi Moriyama; Peronti, Ana Lúcia Benfatti Gonzalez [UNESP] (Magnolia Press, 2025)
The lac insect, Tachardiella ourinhensis Hempel, 1937 (Hemiptera: Coccomorpha: Kerriidae), is redescribed and illustrated based on type material, and transferred to Neotachardiella Kondo, Peronti & Pacheco da Silva, gen. nov. as Neotachardiella ourinhensis (Hempel), comb. nov. Additionally, two new species, Neotachardiella charruarum Kondo, Peronti & Pacheco da Silva, sp. nov. and Neotachardiella nangapire Kondo, Peronti & Pacheco da Silva, sp. nov., are described and illustrated based on adult females collected in Uruguay and Brazil, respectively, on various species of Myrtaceae. In addition, the first-instar nymph of N. charruarum is described and illustrated. A lectotype is designated for T. ourinhensis based on slides mounted from type material deposited at the Instituto Biológico de São Paulo, Brazil. A taxonomic key to separate all known genera of the family Kerriidae and a key to separate the species of Neotachardiella are provided.
Keywords: Insect pest; lac insect; morphology; phylogeny; scale insect; taxonomy; urban pest